2015
DOI: 10.1016/j.febslet.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory complexes III and IV can each bind two molecules of cytochrome c at low ionic strength

Abstract: a b s t r a c tThe transient interactions of respiratory cytochrome c with complexes III and IV is herein investigated by using heterologous proteins, namely human cytochrome c, the soluble domain of plant cytochrome c 1 and bovine cytochrome c oxidase. The binding molecular mechanisms of the resulting cross-complexes have been analyzed by Nuclear Magnetic Resonance and Isothermal Titration Calorimetry. Our data reveal that the two cytochrome c-involving adducts possess a 2:1 stoichiometry -that is, two cytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 68 publications
6
47
0
Order By: Relevance
“…In addition, significant CSPs (Δδ avg ≥ 0.05 ppm) were detected for Lys7, Lys13, His26, Lys39, Ala43, Thr78, Lys86, Lys88, and Glu89. Interestingly, Lys8, Lys13, Lys27, Lys72, and Lys86 also experienced large CSPs, as previously reported for the interaction between WT Cc and Cc 1 (47,48).…”
Section: Phosphorylation Of Tyr48 Enhances Internal Mobility In Cytocsupporting
confidence: 84%
See 4 more Smart Citations
“…In addition, significant CSPs (Δδ avg ≥ 0.05 ppm) were detected for Lys7, Lys13, His26, Lys39, Ala43, Thr78, Lys86, Lys88, and Glu89. Interestingly, Lys8, Lys13, Lys27, Lys72, and Lys86 also experienced large CSPs, as previously reported for the interaction between WT Cc and Cc 1 (47,48).…”
Section: Phosphorylation Of Tyr48 Enhances Internal Mobility In Cytocsupporting
confidence: 84%
“…4B). The fits of CSPs along the titration suggested that Cc 1 binds two Y48pCMF Cc molecules, as previously found with the WT Cc species (47,48) (Fig. 4C).…”
Section: Phosphorylation Of Tyr48 Enhances Internal Mobility In Cytocsupporting
confidence: 83%
See 3 more Smart Citations